Conversor Boost ZCZVT aplicado em um sistema de iluminação de emergência com LED - Amaral, Heberty Huilton (2011)
In this paper we present a study of an emergency lighting system is not permanent. This system consists of batteries, LED boost converter and power. The focus of the paper is to analyze the boost converter, which employs two switching techniques, which are: hard switching and soft switching. The analysis made in the converter are related to the commutation of the main semiconductor switch occur hard or soft switching technique for hard and check for soft switching the switches (main and auxiliary) switch in a hard or soft. Another important fact is to evaluate the performance of the boost converter for the two switching techniques. Also investigated is the autonomy of the emergency lighting system and also if he is quoting in accordance with IEEE 446, regarding the autonomy of the system. Finally is shown the waveform of the current supplied to the LED. In short, the converter that employs the technique of switched hard demonstrated that switching occurs in a hard, since the techniques of soft switching, the switch went soft. The measured efficiency of the converter through the autonomy of the emergency lighting system has proven that soft switching is more efficient than the hard switching, around 34% due to reduction in switching losses. It was reported that the converter with soft switching technique used in emergency lighting system achieved an endurance of one hour and four minutes, as the converter using the switching technique obtained a hard range of forty-two minutes. Therefore, emergency lighting systems, in which the boost converter makes use of two switching techniques are in accordance with IEEE Std-446. In ultimate analysis it was observed that the current supplied to the LED from a converter with soft switching has a ripple around 35% lower than the current coming from a switching converter with hard and does not have oscillation current level, such features increase the lifetime of the LED and do not alter the photometric characteristics of the LED.